2016
DOI: 10.1136/bmjquality.u206305.w4089
|View full text |Cite
|
Sign up to set email alerts
|

Improving communication between phlebotomists and doctors: a quality improvement project

Abstract: Blood tests are a seemingly basic investigation, but are often a vital part of directing patient management. Despite the importance of this everyday process, we indentified the potential for improvement of the current phlebotomy service in our hospital, as both junior doctors and phlebotomists reported a lack of communication and standardised practice across the wards. Resulting delays in obtaining blood test results can impact detrimentally on patient safety and management.We designed a survey which highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
(6 reference statements)
0
7
0
1
Order By: Relevance
“…There were 15 improvement interventions that were created in response to the areas of concern which we tested by completing four PDSA cycles across a 20-week period. 5 Most of the practitioners were amenable to the changes though some areas of anticipated risks for unsuccessful compliance with the new process were the time factor for a proper time-out and filling out the checklist in its entirety given the busy and pressured perioperative environment.…”
Section: Designmentioning
confidence: 99%
“…There were 15 improvement interventions that were created in response to the areas of concern which we tested by completing four PDSA cycles across a 20-week period. 5 Most of the practitioners were amenable to the changes though some areas of anticipated risks for unsuccessful compliance with the new process were the time factor for a proper time-out and filling out the checklist in its entirety given the busy and pressured perioperative environment.…”
Section: Designmentioning
confidence: 99%
“… 1–7 Similar projects have been undertaken both nationally and internationally, which have identified the importance of good communication between staff and service users. Saunsbury et al 1 demonstrated that improved communication between phlebotomist and junior doctors was achieved by the introduction of the phlebotomy box. Sustersic et al reported that patient information leaflets in emergency departments in France improved the overall patient satisfaction with healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…The impact that effective communication has on patient satisfaction has been widely reported in the literature. [1][2][3][4][5][6][7] Similar projects have been undertaken both nationally and internationally, which have identified the importance of good communication between staff and service users. Saunsbury et al 1 demonstrated that improved communication between phlebotomist and junior doctors was achieved by the introduction of the phlebotomy box.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Enfatizar el lado humano que debe tener el perfil del flebotomista como característica principal, tomando en cuenta que es el único dentro del laboratorio clínico que tiene contacto con el paciente. 10 Las actitudes que se mencionan son recomendaciones para el personal que realiza flebotomía, para que le sirvan de herramientas para poder proporcionar un mejor servicio hacia al paciente, esto ayudará a tener una mejor comunicación y relación con el paciente. Sumándole al conocimiento habilidad y competencia, una combinación de métodos un estándar de oro en la medicina de laboratorio.…”
Section: Introductionunclassified